Sportsfreund Lötzsch . Sportsman Lötzsch - Hilpert, Sascha; Prechtel, Sandra (Hanfgarn & Ufer Filmproduktion, 2007)
Verzio FF Submission In the 1970s Wolfgang Lötzsch was one of the most talented cyclists in the German Democratic Republic. An unwilling revolutionary, he refused to be an opportunist within the state sport apparatus and was excluded from the GDR’s program for high-performance athletes because of his critical attitude towards the party and state. Placed under Stasi surveillance, he spent the rest of his career pedaling into a political headwind. Lötzsch battled on alone, recruiting a non-sanctioned coach, who sacrificed his career to help the gifted cyclist. At races, Lötzsch was always the outsider, but he was cheered to victory by a loyal group of fans. For seventeen years, he won race after race, but he was never allowed to compete in a major competition outside the GDR. “Sportsman Lötzsch” tells the story of an apolitical man who embarked on a personal campaign against opportunism, cowardice and betrayal, thereby upsetting the apparatus of a repressive state.